Evaluasi Sistem Informasi Kepegawaian Dengan Standar ISO/IEC 9126 Pada Universitas Jambi - Simatupang, John Devin Junior; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2024)
In the current era of globalization, information technology or software is one of the important resources foran institution or organization. Data processing in software as a strategic decision-making tool must besupported by quality information systems and software. One of the information systems or software thatfunctions to assist management processes is the Human Resource Management Information System. Thequality of this system has a significant impact on the quality of the information generated. The datacollection method used a questionnaire and the data analysis used quantitative descriptive analysis. Theresults of the data analysis show that the average value of Functionality is 3.97, Usability is 3.62, Reliabilityis 4.11, Efficiency is 3.87, Maintainability is 3.63, and Portability is 3.79. In general, the software hasshown good performance or can be categorized as